Cyberterrorism 2 0 or terrorist use of social media: the Islamic State case - Vilar-Lopes, Gills; Medeiros, Marcelo de Almeida (Revista Brasileira de Estudos de Defesa, 2021)
Cyberspace has become a common source of international security threats, especially after September 11. The emergence and popularisation of so-called social media have enhanced the militancy of the most diverse groups, including terrorist ones. This article problematises international terrorism, pointing out the causes and effects of this 21st-century phenomenon that we name cyberterrorism 2.0. Thus, we focus on the cyberterrorism studies that analyse social media usage's inputs and outputs by terrorist groups. Through Webometrics and the framework Stakeholders, Activities and Motives in the realm of cybersecurity (SAM), we aim to explain, in the light of International Security Studies and through the Islamic State case study, how cyberterrorism 2.0 arises, develops and impacts national security.